656 Making an Effective Ward Round Model in the Department of Trauma and Orthopaedic Surgery for University Hospitals of Birmingham Trust. (19th August 2022) - Khaleeq, T; Lo, N; King, J; Turner, A; Howland, E; Graham, T
Abstract: Background: Ward rounds in hospitals are crucial for decision-making in the context of patient treatment processes. Objectives: Improve the standard of ward rounds with a review of care and planning. Method: 6 key elements were established using the Modern ward rounds report by the Royal College of Physicians and Nursing. This includes daily ward rounds which will be multidisciplinary, documented clearly and handed over to relevant staff; consisting of a board, bedside ward round and debrief; using Prompts in the form of REMIND mnemonic : R = Respect form, E = Electronic Prescribing, M = Mental Capacity, mobility status, I = Investigations, N = Nutrition and Hydration, NBM status, D=DVT assessment and Thromboprophylaxis; with practices being audited. Results: After running a successful pilot in Respiratory in August 2021 the quality improvement project (QIP) was introduced in Trauma and Orthopaedic surgery. 88 patients were included in the initial audit prior to implementation and 91 in the re-audit. There was a 85% improvement seen in completion of respect and dementia forms with a 90% improvement in electronic prescribing. There was an 75% improvement in documentation of mobility status, investigations performed and NBM status. Fluid prescription, DVT assessment and LMWH prescription also improved by 85%. Conclusions: A successful Pilot in Respiratory and Trauma and Orthopaedic Surgery shows the feasibility of the QIP in other departments. However, Education should also include Consultant and nurses. We are overcoming this but establishing a virtual module that can be made mandatory for induction of junior doctors, consultants, and nurses.